Graphic organizer: Methodological strategy for meaningful student learning - Poma Solier, Teodosio Zenobio (Jurnal Cakrawala Pendidikan, 2025)
The complexity of explaining and describing educational phenomena poses a significant challenge for educators, who must convey information effectively through pedagogical mediation and structured methodologies. This study investigates the impact of graphic organizers as a methodological strategy to enhance meaningful learning in Educational Management. Employing a quantitative quasi-experimental design, the research utilized observation and surveys as data collection techniques, with a checklist and the ACRA Scale on Learning Strategies as instruments. The study involved 57 students, divided into an experimental group (n = 29) and a control group (n = 28), who underwent pre-test and post-test evaluations. Findings indicate a statistically significant difference between the two groups, supporting the alternative hypothesis. The experimental group exhibited substantial improvements across conceptual, procedural, and attitudinal learning dimensions, reinforcing the effectiveness of graphic organizers in fostering structured knowledge acquisition and cognitive development. The post-test results demonstrated higher retention rates and deeper comprehension among students who utilized graphic organizers. The study concludes that graphic organizers enhance meaningful learning by providing visual structures that facilitate information processing and conceptual connections. These findings underscore the importance of integrating structured pedagogical tools in higher education to stimulate critical thinking, improve content retention, and promote autonomous learning. Future research should explore the long-term effects of graphic organizers across diverse academic disciplines to validate their broader applicability in educational settings.